2019
DOI: 10.3389/fonc.2019.00682
|View full text |Cite
|
Sign up to set email alerts
|

Papillomavirus Immune Evasion Strategies Target the Infected Cell and the Local Immune System

Abstract: Persistent infection with human papillomavirus (HPV) initiates ~5% of all human cancers, and particularly cervical and oropharyngeal cancers. HPV vaccines prevent HPV infection, but do not eliminate existing HPV infections. Papillomaviruses induce hyperproliferation of epithelial cells. In this review we discuss how hyperproliferation renders epithelial cells less sensitive to immune attack, and impacts upon the efficiency of the local immune system. These observations have significance for the design of thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
135
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(160 citation statements)
references
References 211 publications
(236 reference statements)
2
135
0
6
Order By: Relevance
“…By ESTIMATE algorithm, we first found that high immune scores were related to better OS, which is consistent with the results of previous studies showing that immune cells infiltrating the tumor tissue may inhibit cancer cells (Cho et al, 2014;Gorter et al, 2015). The study also found HPV-positive cases had higher immune scores than HPV-negative cases, which might be associated with HPV-related microenvironment components regulation, such as increase of regulatory immune responses and decrease of effector immune responses (Zhou et al, 2019). A total of 1367 DEGs between the low-and high-immune score groups were identified, and 401 DEGs among them were related to survival outcomes of cervical cancer patients.…”
Section: Discussionsupporting
confidence: 89%
“…By ESTIMATE algorithm, we first found that high immune scores were related to better OS, which is consistent with the results of previous studies showing that immune cells infiltrating the tumor tissue may inhibit cancer cells (Cho et al, 2014;Gorter et al, 2015). The study also found HPV-positive cases had higher immune scores than HPV-negative cases, which might be associated with HPV-related microenvironment components regulation, such as increase of regulatory immune responses and decrease of effector immune responses (Zhou et al, 2019). A total of 1367 DEGs between the low-and high-immune score groups were identified, and 401 DEGs among them were related to survival outcomes of cervical cancer patients.…”
Section: Discussionsupporting
confidence: 89%
“…If metastasis and infiltration occur, the treatment effect of cervical cancer patients will become very unsatisfactory. In recent years, immunotherapy has performed well in a variety of cancers including cervical cancer [25][26][27] . Blocking PD-L1 / PD-1 signaling pathway to attack tumor cells expressing PD-L1 is the current mainstream method 28 .…”
Section: Discussionmentioning
confidence: 99%
“…С другой стороны, было показано, что иммунная толерантность способствует персистенции вируса и прогрессированию рака [5]. В то же время не исключено влияние двух основных классов генов, участвующих в развитии РШМ, -онкогенов и генов-супрессоров опухолей.…”
Section: материалы и методы / Materials and Methodsunclassified